Physiological fitness profile of NCAA Division I female field hockey players - Smith, V. G.; Jayaraman, R. C. (ARC Journal of Research in Sports Medicine, 2019)
Field hockey, one of the world`s oldest competitive sports, requires high levels of muscular strength and endurance. Despite its worldwide popularity, little is known about the physiological fitness profile of collegiate female field hockey player. The purpose of our study was to measure the physiological fitness and lipid profiles of collegiate female field hockey athletes. Fifteen female members of an NCAA Division I Field Hockey team (age 19.9 ± 1.1 years, height 161.4 ± 7.0 cm, mass 61.1±10.9 Kg) completed the following assessments, body composition (hydrostatic weighing) to evaluate percent body fat (%BF), body mass index (BMI), and incremental treadmill (modified Bruce Protocol) to assess maximal oxygen uptake (VO2max), and isokinetic strength (CYBEX Norm Dynamometer) to measure knee extensor and flexor muscle group peak torque production. Fasting blood samples were also collected and analyzed at our local clinic by licensed clinical staff. Study participants tested at a higher fitness level than previously reported in literature, relative VO2max: 55.77 ± 4.70 ml/kg/min (mean ± SD), absolute VO2max: 3.38 ± 0.50 L/min, %BF: 22.39 ± 0.05, BMI: 23.67 ± 3.08, right H:Q (75 ± 21%), left H:Q (77 ± 18.5%) and peak torque: 69.83 ± 18.88 ft/lbs. Fasting glucose (91.33 mg/dl ± 2.39), triglycerides (82.27 mg/dL ± 8.17), total cholesterol (176.13 mg/dl ± 10.09), low-density lipoprotein cholesterol (98.13 mg/dL ± 9.22), high-density lipoprotein cholesterol (61.6 mg/dL ± 3.57) were all within recommended range outlined in the Adult Treatment Panel (ATP III). Collegiate female field hockey athletes scored high in muscular strength and aerobic capacity. In addition, their blood lipid profiles and serum glucose concentration were well within the recommended range for age and gender.